Autonomous Vehicle and Smart Traffic 2020
DOI: 10.5772/intechopen.85707
|View full text |Cite
|
Sign up to set email alerts
|

Vehicular Noise Pollution: Its Environmental Implications and Strategic Control

Abstract: Noise pollution has been recognized as one of the major hazard that impacts the quality of life all around the world. Because of the rapid increase in technology, industrialization, urbanization and other communication and transport systems, noise pollution has reached to a disturbing level over the years which needs to be studied and controlled to avoid different health effects like high blood pressure, sleeplessness, nausea, heart attack, depression, dizziness, headache, and induced hearing loss. To address … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(11 citation statements)
references
References 119 publications
1
10
0
Order By: Relevance
“…It has also been reported that noise pollution in colleges results in annoyance, lack of concentration, speech interference, stress, low productivity, increased absenteeism, and other negative effects (Obot & Ibanga, 2013). Students learning outcomes have been significantly impacted by their learning environment; and noise has been observed to be one of the main factors that distracted pupils, impaired their ability to pay attention and concentrate, and caused headaches and anxiety (Farooqi et al, 2020). A noise pollution survey conducted in an educational institute observed that 62% of people had a disturbance in the teaching-learning process, 18% for classroom discussion, and 20% had health problems and mental stress (Debnath et al, 2012), as shown in Fig.…”
Section: Noise and Public Healthmentioning
confidence: 99%
“…It has also been reported that noise pollution in colleges results in annoyance, lack of concentration, speech interference, stress, low productivity, increased absenteeism, and other negative effects (Obot & Ibanga, 2013). Students learning outcomes have been significantly impacted by their learning environment; and noise has been observed to be one of the main factors that distracted pupils, impaired their ability to pay attention and concentrate, and caused headaches and anxiety (Farooqi et al, 2020). A noise pollution survey conducted in an educational institute observed that 62% of people had a disturbance in the teaching-learning process, 18% for classroom discussion, and 20% had health problems and mental stress (Debnath et al, 2012), as shown in Fig.…”
Section: Noise and Public Healthmentioning
confidence: 99%
“…[5][6][7]9,[19][20][21][22] Exposure to high noise levels from workshops/laboratories cause disturbances in teaching-learning process, such as classroom discussion, task performance, problem-serving and mental stress. 14,20,[23][24][25][26] Therefore, it is crucial to utilize efficient acoustic (sound insulation) or sound absorption materials in workshops/ laboratories in educational institutes for noise mitigation.…”
Section: Introductionmentioning
confidence: 99%
“…57,9,19–22 Exposure to high noise levels from workshops/laboratories cause disturbances in teaching-learning process, such as classroom discussion, task performance, problem-serving and mental stress. 14,20,23–26…”
Section: Introductionmentioning
confidence: 99%
“…Sheikh et al [8] stated that excessive noise affects hearing loss. Farooqi et al [9] pointed out that excessive noise causes high blood pressure, heart disease, and headache. Basner and McGuire [10] examined the effect of noise on sleep and stated that noise decreases sleep continuity, decreases total sleep time, and causes fragmented sleep.…”
Section: Introductionmentioning
confidence: 99%
“…The results of industrial noise levels in Oran demonstrated that noise levels were ranged from 95 to 115 dBA. Farooqi et al [9] emphasized that different industries such as the textile industry, wood industry, and steel mills have different machines. In summary, it is understood that there can be many different types of noise sources in industrial noise analysis, and all different types of industrial noise sources may need to be considered in noise analysis.…”
Section: Introductionmentioning
confidence: 99%